Management of Hypertension in Elderly - Khazaal, Faris AK; Abdulaziz, Lewai S; Abdulaziz, Lewai S; Marzook, Ahmed Abed (AL-Kindy College Medical Journal, 2014)
Background:The document on hypertension in the elderly promoted by the American college of cardiology and the American heart association (ACCF/AHA) was written with the intent to be a complete reference at the time of publication on the topic of managing hypertension in the elderly. More recently, the European society of hypertension (ESH) and the European society of cardiology (ESC) issued the 2013 ESH/ESC Guidelines for the management of arterial hypertension, followed by The 2014 Canadian Hypertension Education Program (CHPE), and the Eighth Report of the Joint National Committee (JNC8), all of which has endorsed specific recommendations for the management of elderly hypertensive patients.